High frequency of copy number variations and sequence variants at CYP21A2 locus: implication for the genetic diagnosis of 21-hydroxylase deficiency. - Silvia Parajes; Celsa Quinteiro; Fernando Domínguez; Lourdes Loidi (PLoS ONE, 2008)
The systematic study of the human genome indicates that the inter-individual variability is greater than expected and it is not only related to sequence polymorphisms but also to gene copy number variants (CNVs). Congenital Adrenal Hyperplasia due to 21-hydroxylase deficiency (21OHD) is the most common autosomal recessive disorder with a carrier frequency of 1:25 to 1:10. The gene that encodes 21-hydroxylase enzyme, CYP21A2, is considered to be one of the most polymorphic human genes. Copy number variations, such as deletions, which are severe mutations common in 21OHD patients, or gene duplications, which have been reported as rare events, have also been described. The correct characterization of 21OHD alleles is important for disease carrier detection and genetic counsellingCYP21A2 genotyping by sequencing has been performed in a random sample of the Spanish population, where 144 individuals recruited from university students and employees of the hospital were studied. The frequency of CYP21A2 mutated alleles in our sample was 15.3% (77.3% were mild mutations, 9% were severe mutations and 13.6% were novel variants). Gene dosage assessment was also performed when CYP21A2 gene duplication was suspected. This analysis showed that 7% of individuals bore a chromosome with a duplicated CYP21A2 gene, where one of the copies was mutated.As far as we know, the present study has shown the highest frequency of 21OHD carriers reported by a genotyping analysis. In addition, a high frequency of alleles with CYP21A2 duplications, which could be misinterpreted as 21OHD alleles, was found. Moreover, a high frequency of novel genetic variations with an unknown effect on 21-hydroxylase activity was also found. The high frequency of gene duplications, as well as novel variations, should be considered since they have an important involvement in carrier testing and genetic counseling.